2006
DOI: 10.1063/1.2372498
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic transfer of population in a dense fluid: The role of dephasing statistics

Abstract: We report the results of simulation studies of the statistics of vibrational dephasing of a YCl (Y=H, D, T, and I) diatom in dense fluid Ar at two temperatures, including the effect of strong field driving on the energy level modulation statistics. The distribution of energy level modulations is found to be non-Gaussian with a high energy tail. Aspects of stimulated Raman adiabatic passage (STIRAP) between the vibrational levels of HCl in dense fluid Ar have been investigated. For HCl with nearly degenerate v=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…3 This study showed that for pulse lengths of a few picoseconds the robustness of STIRAP disappeared as soon as the additional background couplings exceeded about one tenth of the two basic STIRAP couplings, an effect attributed, in part, to the multitude of single-and multiphoton transitions that contribute to the elaborate linkage pattern. Similar studies were presented by Demirplak and Rice (2002) and Demirplak and Rice (2006), who used a much smaller set of states and were therefore led to conclude that STIRAP may be possible for such a system.…”
Section: Stirap In a Dense Web Of Molecular Statessupporting
confidence: 66%
“…3 This study showed that for pulse lengths of a few picoseconds the robustness of STIRAP disappeared as soon as the additional background couplings exceeded about one tenth of the two basic STIRAP couplings, an effect attributed, in part, to the multitude of single-and multiphoton transitions that contribute to the elaborate linkage pattern. Similar studies were presented by Demirplak and Rice (2002) and Demirplak and Rice (2006), who used a much smaller set of states and were therefore led to conclude that STIRAP may be possible for such a system.…”
Section: Stirap In a Dense Web Of Molecular Statessupporting
confidence: 66%
“…The robust control study would be performed in the following artificial quantum system (Figure 2 and Figure 3), which is closely related to atomic quantum systems like atomic Rb used in experimental quantum learning control [4,39]: We note that a variety of quantum control systems previously studied, including both molecular and spin states, can be described by Hamiltonians of Hilbert space dimension similar to that above and are amenable to modelbased control, rendering the robust control of systems such as our example system important in practice. In the context of atomic and molecular systems, the control of subspectra similar to that above has been studied using the STIRAP method [40][41][42]. More generally, robustness to uncertainty in a small number of Hamiltonian parameters is important in a variety of quantum control applications including quantum information processing, where for example coupling strengths between subsystems may be imprecisely known based on first principles [30].…”
Section: Robust Control Optimization Via Multiobjective Evolutionary ...mentioning
confidence: 99%
“…Concurrently, there were theoretical studies of energy flow among vibrations in polyatomic molecules and of different approaches to unimolecular reaction rate theory (72-79). In turn, these studies led to the examination of the role of deterministic classical-mechanical chaos in unimolecular reactions (80-92), of quantum chaos and its relevance to chemical reactions (93)(94)(95)(96)(97)(98), and development of the theory of optical control of molecular dynamics (99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118).…”
Section: From Radiationless Transitions To Quantum Controlmentioning
confidence: 99%
“…Because electronic dephasing occurs on the femtosecond time scale, the objective was to control molecular dynamics within the manifold of vibrational states on the ground electronic state. Demirplak (115)(116)(117)(118) showed that there can be efficient population transfer, and control of a product branching ratio, under specified conditions for the ratio of the Rabi frequency to the frequency of energy-level fluctuations. Gong (110,111) later showed that adiabatic population transfer in a liquid remains robust even when decaying states are involved.…”
Section: From Radiationless Transitions To Quantum Controlmentioning
confidence: 99%